Effects of Rainwater Harvesting Techniques on Establishment and Survival of Acacia senegal (L.) Transplants on Dry Lands in South Darfur State, Sudan - Omer, Adam ZaKaria Abdalla; Ahmed, Daldoum Mohammed (University of Khartoum Journal of Agricultural Sciences, 2021)
The study was conducted in South Darfur State in Nyala Agricultural Research Station Farm which is located at latitude 12° 01ʹ N and longitude 24° 50ʹ E and at an altitude of 400 m a.s.l, during two seasons 2018 and 2019. The study aimed to test and assess the effects of rainwater harvesting techniques (RWHTs) on establishment, growth and survival rate of Acacia senegal transplants on dry land, to assess its influence on soil moisture content. Four RWHTs were tested namely; control, semicircular bund, trapezoidal bund and V-shape catchment. The treatments were arranged in randomized complete block design with six replications. The soil moisture content (gravimetric) at depths of 0-20, 20-40 and 40-60 cm during the (summer, autumn and winter) were measured .Tree state as survival rate, growth parameters of shoot height, stem diameter, number of branches, root length, shoot and root biomass were measured. The results showed that the RWHTs recharged considerably the soil moisture content in all the depths in autumn, including the control. The transplants' survival rates were better in the RWHTs than in the control and in summer 2019 the survival percentages in these treatments ranged from 67 % to 75 % against 50 % only for the control. The trapezoidal bund showed the most resistant against the transplants' death rate. Significant differences were found in the A. senegal transplants growth parameters between the control and the RWHTs. The overall growth performance within the RWHTs was as follows, trapezoidal bund > semicircular bund = V-shape catchment > control. It is thus evident that RWHTs can be used to support establishment of transplants in the moistures content deficient areas of dry lands. The study concluded that RWHTs can be applied using manual labor and locally available materials. Further research should focus on RWHTs as worthy option for tree plantation in dry land.